Meaning Construction In Porn Film Indonesia Phenomenology studies Widescreen Film Producers in Jakarta - S. Utari Widyastuti (KOM & REALITAS SOSIAL, 2011)
This study aims to find out the meaning of pornography on the big screen movie producer Indonesia, and to know the motives and experiences of pornography in the film. The research question posed is: What meaning producers of pornography in the film? What was the motive for producers include aspects of pornography in movies? How does the experience of producers of pornography?This is a qualitative research method with the tradition of phenomenology. The subject of his research is the producer of feature films Indonesia in Jakarta. The object of research is the construction of meaning, motives and experiences. The collection of data obtained through observation, in-depth interviews carried out on the big screen movie producer Indonesia in Jakarta as an informant. Data were obtained through library research and documentation of various media, both print and online.The results widescreen film producer Indonesia over the meanings of pornography different from each other depending on experience and cognitive complexity of each individual. Also because of information about itself or pornographic pornography in the film. Motif also affected the internal and external factors produse itself. Experience more supportive if the producers will continue to provide aspects of pornography in his movie or not . The conclusion of this study is the construction of meaning widescreen film producer Indonesia to pornography vary. Motive incorporate different aspects of pornography. Pengalamannyapun different. Theoretically penelitin is the continuation of the behavior of nonverbal communication that is so luas.Saran film producer practical, film producer through the construction of meaning and experience of entering the positive aspects of pornography can be distributed to others. While the construction of meaning and negative experiences can be a lesson and inputs for producers of other films.